Two-step regulation of trachealess ensures tight coupling of cell fate with morphogenesis in the Drosophila trachea - Kondo, Takefumi (eLife, 2019)
During organogenesis, inductive signals cause cell differentiation and morphogenesis. However, how these phenomena are coordinated to form functional organs is poorly understood. Here, we show that cell differentiation of the Drosophila trachea is sequentially determined in two steps and that the second step is synchronous with the invagination of the epithelial sheet. The master gene trachealess is dispensable for the initiation of invagination, while it is essential for maintaining the invaginated structure, suggesting that tracheal morphogenesis and differentiation are separately induced. trachealess expression starts in bipotential tracheal/epidermal placode cells. After invagination, its expression is maintained in the invaginated cells but is extinguished in the remaining sheet cells. A trachealess cis-regulatory module that shows both tracheal enhancer activity and silencer activity in the surface epidermal sheet was identified. We propose that the coupling of trachealess expression with the invaginated structure ensures that only invaginated cells canalize robustly into the tracheal fate.